Preliminary Condition Analysis of Samadhi Dewan Sawan Mal, Multan - Jahanzaib Qamar; Dr. Saima Gulzar; Zahid Iqbal (Sir Syed University Research Journal of Engineering and Technology)
Historic structures are unparalleled jewels of the past embedded in the built environment. They integrate the present society with the past and future through its historic fabric existence over the decades. The negligence due to the economic dilemma in our part of the world is one of the major reasons of the disappearance of many such historic structures. Building condition assessment tool is very useful in decision making for such historic structures that can be saved for the future generations within the available resources through the maintenance prioritization listing developed regionally. The presented research was carried out on one of the historic structure Samadhi Dewan Mal situated in Multan (which is known as the city of saints). The city of Multan displays rich historical evidences in the form of tombs, mosques, historic residential houses, palaces, temples and archaeological sites. Through the visual analysis in addition to the damage identification and observations maintenance matrix was developed for different parts of the historic structure that can be replicated for other structures/ sites as well to stop further destruction of neglected heritage. The concluded rating of Samadhi Dewan Mal placed it in medium condition that needs repair strategy to regenerate its original essence with authenticity.